Integrating Folktales Teaching in Improving Students’ Writing Skills - Stephanie Yakumbu; Darni Darni; Resdianto Permata Raharjo (Journal of Education and Teacher Training Innovation, 2024)
This paper aims to explore the role of folktales in enhancing students’ writing skills in English learning classrooms. It is expected to be used as a teacher guide in teaching and learning by teaching students in improving creative writing skills in Papua New Guinea primary educations where students lack good English writing skills. This literature analysis shows that by integrating of folktales students can improve their writing skills. In addition, students will develop critical thinking skills. The research method involved collection of previous studies of folktales and folklores studies done by researchers and the conclusions they suggested after their primary and secondary researches. I analysed 14 previous studies in a able to look for patterns and synthesises on it. The analysis is made by looking at reoccurring benefits that was discussed in the studies. This article supports the integration of utilizing fairy tales and fables, that students are familiar with, Teachers can assist students in connecting with the material and gaining a deeper understanding of it. Careful planning is needed to execute this approach. This tool designed to improve students’ creative-writing skills.